Analisis Forecasting Penjualan Pupuk Bersubsidi Menggunakan Metode Peramalan Dekomposisi Time Series PT Pupuk Indonesia Persero - Markus Rivaldo Yulinchton; Alfatih S. Manggabarani; Maria Assumpta Wikantari; Prasetyo Hadi (LP2M IAIN Palopo, 2025)
The purpose of this study is to provide the best forecasting solution related to subsidized fertilizers at PT Pupuk Indonesia. This research is quantitative in nature, utilizing secondary data from the Annual Report of PT Pupuk Indonesia (Persero). The study employs the Weighted Moving Average (WMA) calculation method with weights of 3, 5, and 7, and uses the Mean Absolute Percentage Error (MAPE) index to measure the accuracy of the generated data. The analysis results indicate that the sales forecasting using the WMA method with weights of 3, 5, and 7 can be recommended, as the MAPE values fall within the range of 10%-20%, which is categorized as having good predictive capability.